On the Diophantine Equation x2 kxy + ky2 + ly = 0, l = 2n - Sukrawan Mavecha (My University, 2017)
Abstract We consider the Diophantine equation x 2 -kxy+ky 2 + ly = 0 for l = 2 n and determine for which values of the odd integer k, it has a positive integer solution x and y.
Keywords: Advanced Mathematical Theories and Applications